2012
DOI: 10.1597/10-238
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Morphometric Developments of the Maxillary and Mandibular Arches during the Fetal Period

Abstract: Data obtained in the study would be useful for clinicians by presenting an objective scale related to the prenatal period as well as being helpful in assessing the development of this region, identifying the anomalies and pathologies, and assisting treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…The convexity and the shape of the fetal face in the sagittal section have minimal change during the third trimester, with only the size of fetal face steadily increasing. In the late trimester, the mandible grows mainly in the width dimension, changing from triangular shape to square shape . Roelfsema et al also found the mandibular forward growth, which was expressed by the decrease in mid‐ to lower facial depth ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The convexity and the shape of the fetal face in the sagittal section have minimal change during the third trimester, with only the size of fetal face steadily increasing. In the late trimester, the mandible grows mainly in the width dimension, changing from triangular shape to square shape . Roelfsema et al also found the mandibular forward growth, which was expressed by the decrease in mid‐ to lower facial depth ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The boundaries of the alveolar arches on the casts were outlined on acetate to get the shapes of the arches (Fig. 2; Esenlik et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Dichos resultados coinciden con nuestro estudio, puesto que se encontró que conforme aumenta la edad gestacional, regularmente las dimensiones del paladar también aumentan, sin embargo; dicho aumento no genera diferencias significativas en el índice palatino de neonatos pre-término y neonatos a término. Nuestros resultados también coinciden con los estudios de Esenlik et al (2012)18 quienes realizaron un estudio de las dimensiones del paladar en material fetal con edades entre 8-y 40 semanas de gestación y concluyeron que los índice palatal y mandibular, no cambian durante la vida prenatal.…”
unclassified